Can low grade PMP be divided into prognostically distinct subgroups based on histological features? A retrospective study and the importance of using the appropriate classification. Issue 7 (July 2018) - Bhatt, Aditi; Mishra, Suniti; Prabhu, Robin; Ramaswamy, Veena; George, Antony; Bhandare, Sonal; Shah, Mita; Mehta, Sanket
Abstract: Introduction: The pathological classification of PMP of appendiceal origin has prognostic and treatment implications. Our goals were to Classify low grade mucinous carcinoma peritonei (LGMCP) into prognostically distinct subgroups based on histological features. Compare the reproducibility of the WHO and the PSOGI classifications for both PMP and the appendiceal primary tumor. Patients and methods: A retrospective analysis of patients undergoing CRS and HIPEC or debulking surgery was done. All the tumors were re-classified according to the PSOGI classification. LGMCP was further classified into three histological subgroups and the impact on survival was evaluated. Results: From Jun 2011 to June 2016, 101 patients underwent CRS with HIPEC (n = 89) or debulking surgery (n=12). The median PCI was 28 (3–39) and 74.1% patients had CC-0/1 resections. Of the 76.2% patients who had LGMCP, 4 patients (5.1%) were classified as group 1, 54 (70.1%) as group 2 and 19 patients (24.6%) as group 3. At a median follow up of 21 months, the disease free survival was not reached, 30 months and 14 months for groups 1, 2 and 3 respectively (p = 0.09). There was no difference in overall survival. Using the WHO classification, there was a discordance in the grade of the primary tumor and the peritoneal lesions in 19.8% and conflicting terminology was used in 62% of patients. Conclusions: The subgroups of LGMCP described here are prognostically different though this needs further prospective evaluation in larger series. The PSOGI classification is more uniformly reproducible and should be preferred to the WHO classification.